The Effect of Price and Promotion on Honda Beat Customer Loyalty (Case Study on Honda Saudara Motorcycle Dealership in Solok City) - Syaiful, Syaiful; Fauzyyah , Assyfa (Adpebi Science Series, 2024)
Customer loyalty is a positive attitude given by consumer satisfaction with a product or company which ismanifested by the behavior of intending to buy again or who have made repeated purchases to recommend it to anyonethey know.This study aims to see the influence of price and promotion on customer loyalty at Honda Saudara MotorDealers in Solok City.This type of research is an associative research where it aims to find out the relationship between two or more variablesby taking a sample of 100 respondents. The data collection technique in this research is using a questionnaire with aLikert scale. Based on the results of the calculation of the SPSS program application from the t-test, a price variablewas obtained with at-value of -3.369 < t, table 1.660 and a sig value of 0.001 < 0.05 so that H1 was rejected and H0 wasaccepted. In the promotion variable, the value of tis calculated at 5.583 > ttable is 1.660 and the sig value is 0.000 < 0.05 sothat H1 is accepted and H0 is rejected.The results of the F test of significant probability Fcalculated 20.819 > Ftable 3.090 with a significant value of0.000 < 0.05 so that this means that the price has a negative effect on customer loyalty and the promotion has a positiveand significant effect on Honda Beat customer loyalty at Honda Brother Motor Dealers in Solok City.In this study, the determination coefficient is 0.300 or 30%. Where price variables and promotions have aneffect of 30% on Honda Beaat customer loyalty at Honda Saudara Motor Dealers in Solok City. Meanwhile, the other70% was influenced by other variables that were not discussed by the researcher in his study.